2019
DOI: 10.1101/598334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Function and clinical relevance of RHAMM isoforms in pancreatic tumor progression

Abstract: The receptor for hyaluronic acid-mediated motility (RHAMM) is upregulated in various cancers.We previously screened genes upregulated in human hepatocellular carcinomas for their metastatic function in a mouse model of pancreatic neuroendocrine tumor (PNET) and identified that human RHAMM B promoted liver metastasis. It was unknown whether RHAMM B is upregulated in pancreatic cancer or contributes to its progression. In this study, we found that RHAMM protein was frequently upregulated in human PNETs. We inves… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…1D). We have reported that BON1 cells upregulate RHAMM, especially RHAMM B isoform, compared to normal human islets 18 . We incubated BON1_TGL_shLacZ and BON1_TGL_shRHAMM cells with Au/L/HA NPs for 12 h and then imaged the cells under fluorescence microscope.…”
Section: Rhamm B Is Crucial In Pnets and Mediates Cellular Uptake Of mentioning
confidence: 84%
See 4 more Smart Citations
“…1D). We have reported that BON1 cells upregulate RHAMM, especially RHAMM B isoform, compared to normal human islets 18 . We incubated BON1_TGL_shLacZ and BON1_TGL_shRHAMM cells with Au/L/HA NPs for 12 h and then imaged the cells under fluorescence microscope.…”
Section: Rhamm B Is Crucial In Pnets and Mediates Cellular Uptake Of mentioning
confidence: 84%
“…To validate the critical role of human RHAMM B in metastatic progression of PNETs 18 , we generated a new batch of mouse PNET N134 cells expressing human RHAMM B . The expression of human RHAMM B (~82 kDa) was verified in the new N134-RHAMM B cell line by Western blotting using an antibody specific against human RHAMM (Fig.…”
Section: Rhamm B Is Crucial In Pnets and Mediates Cellular Uptake Of mentioning
confidence: 99%
See 3 more Smart Citations